Behavioral Covenants in Congregations: A Handbook for Honoring Differences - Rendle, Gil (Rowman & Littlefield Publishers, 1998)
This down-to-earth workbook gets to the heart of modern congregational life: how to live creatively together despite differences of age, race, culture, opinion, gender, theological or political position. Alban Senior Consultant Gil Rendle explains how to grow by valuing our differences rather than trying to ignore or blend them. He describes a method of establishing behavioral covenants that includes leadership instruction, training tools, resources (visual models, examples of specific covenants), small-group exercises, plans for meetings and retreats.